Principle of compatibility and non-generalised coordinates - Phong, Dinh Van (Vietnam Journal of Mechanics, 2005)
The contribution is devoted to using so-called non-generalised coordinates for deriving the system of equations of motion. Differently from common techniques for constrained mechanical systems the principle of compatibility is chosen as the tool. This takes the advantage in the possibility for extension to systems with nonideal constraints, however, the special treatment is needed. In the article the author derived the theoretical basis as well as numerical algorithms concerning the combination of nongeneralised coordinates with the principle of compatibility. Some comparisons of the technique under consideration and usual technique using Lagrange multipliers are discussed. Some examples are shown for illustration. The case of contact of moving disc on the surface is given in detail